2018
DOI: 10.1007/s00392-018-1232-4
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon versus radiofrequency ablation for paroxysmal atrial fibrillation: a meta-analysis of randomized controlled trials

Abstract: Our systemic review and meta-analysis revealed further evidence that cryoballoon ablation is an equally effective alternative procedure to the standard radiofrequency treatment with a slightly, non-significant higher freedom from AF 1 year after the ablation and a shorter procedure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 38 publications
2
39
0
2
Order By: Relevance
“…Out of the patients with reablation, we noted three patients with recurrence, the remainder were free from arrhythmias since the last procedure. With a recurrence rate around 30% after 12 months, previous publications reported comparable midterm results of CB‐guided AF ablation compared with conventional RF ablation 2,9,13,17 . This might be explained by our relatively healthy patient cohort with low comorbidities and fibrotic burden.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Out of the patients with reablation, we noted three patients with recurrence, the remainder were free from arrhythmias since the last procedure. With a recurrence rate around 30% after 12 months, previous publications reported comparable midterm results of CB‐guided AF ablation compared with conventional RF ablation 2,9,13,17 . This might be explained by our relatively healthy patient cohort with low comorbidities and fibrotic burden.…”
Section: Discussionsupporting
confidence: 53%
“…Pulmonary vein isolation (PVI) is considered as a first‐line treatment in patients suffering from paroxysmal atrial fibrillation (AF) and is regularly performed in patients with drug‐refractory AF 1 . Besides the conventional approach using radiofrequency (RF) energy, cryoballoon (CB) has emerged as a promising technique for successful and durable PVI 2 . In this context, the second generation CB (Arctic Front Advance™; Medtronic Inc., Minneapolis, MN, USA) was designed to further improve the acute efficacy of this single‐shot device for PVI.…”
Section: Introductionmentioning
confidence: 99%
“…In group A (conventional group), the degree of PV occlusion prior to each freeze cycle was filmed (cine run). In group B (intervention group), the following modifications were made: (1) degree of PV occlusion prior to each freeze cycle was only visualized by fluoroscopy and stored with the "store fluoroscopy" function (no cine run); (2) increased radiation awareness (e.g., optimal collimation, minimizing distance between patient and detector, limiting fluoroscopy) ( Fig. 1).…”
Section: Fluoroscopy Settingsmentioning
confidence: 99%
“…PVI is the cornerstone of AF ablation and most patients with AF will receive only a PVI during their index ablation procedure. Previous studies have shown that the clinical efficacy and safety of PVI using either RF or CB ablation is comparable [1,2,9], independent of the use of contact-force catheters and the type of AF (paroxysmal versus non-paroxysmal) [3,[10][11][12]. During the past decade, CB ablation has emerged as an attractive single-shot alternative to RF ablation.…”
Section: Advantages Of Cryoballoon Ablationmentioning
confidence: 99%
See 1 more Smart Citation